Clean and Green Approach for One-pot Synthesis of Pyrazines from Ethylenediamine and 1, 2-Diketone or Its Analogues Under Neat Reaction Condition - Ghosh, Pranab; Chakraborty, Rakesh R. (Letters in Organic Chemistry, 2017)
Background: Compounds having N-heterocyclic moieties are of huge importance in the field of agrochemical, pharmaceutical, biological, fragrances, etc. Due to a lot of applications associated with pyrazine moieties, their synthesis has always been important for organic chemists. Method: Surfeit synthetic methodologies are documented in literature. Most of the methodologies used expensive solvents, harmful metal catalyst and all suffer from rigorous work-up procedures. An efficient, environmentally benign methodology, needs to be developed. We mixed ethylenediamine (2mmol) with 1,2-diketone(1mmol), later, α-hydroxy ketone and α-bromo ketone on magnetic stirrer at room temperature under neat reaction condition for 5 to 10 hrs. Results: After purification by column chromatography using silica gel(60-120 mesh) and pet-ether, ethylacetate mixture as eluent, we achieved pyrazine derivatives from moderate to high yield. Conclusion: Efficient and clean procedure for one-pot preparation of pyrazines from ethylenediamine and 1,2-diketones or with α-hydroxy ketone or with α-bromo ketone has been carried out under neat reaction condition at room temperature. Environmentally benign process furnishing moderate to excellent yields of the product and simple work-up giving pure products are special features of this reaction.
Keywords: ethylenediamine